400 budget best-ever recipes : how to create fuss-free, economical and delicious dishes for all the family, with fabulous recipes shown step by step in more than 1800 beautiful photographs - Doncaster, Lucy (Wigston, Leicestershire : Lorenz Books, 2011)
With 400 delicious, healthy and economical dishes, ranging from soups, appetizers and vegetarian main dishes to meat, fish, desserts, breads and preserves, this is the perfect book for anyone on a tight budget who does not want to sacrifice flavour, nutritional values and the enjoyment and satisfaction of making good food for loved ones.
What is clever cooking? -- How to be a clever cook? -- Sensational soups -- First courses and finger food -- Substantial salads -- Versatile vegetable dishes -- Perfect pasta, beans, and grains -- Fabulous fish and shellfish -- Perfect poultry -- Marvellous meat -- Scrumptious side dishes -- Delectable desserts -- Cakes and bakes -- Classic preserves -- Back to basics.
Includes index.
Keywords: LOW BUDGET CCOKING